Species-Specific and Pollution-Induced Changes in Gene Expression and Metabolome of Closely Related Noccaea Species Under Natural Conditions - Valentina Bočaj; Paula Pongrac; Sina Fischer; Matevž Likar (Plants)
Hyperaccumulators within the Noccaea genus possess many promising genetic and metabolic adaptations that could be potentially exploited to support phytoremediation efforts and/or crop improvement and biofortification. Although hyperaccumulation is very common in this genus, individual species display specific traits as they can accumulate different elements (e.g., zinc, cadmium, and/or nickel). Moreover, there appears to be some populational variability with natural selection increasing the metal tolerance in metallicolous populations. Therefore, employing robust methods, such as integrated analysis of the transcriptome and metabolome, is crucial for uncovering pivotal candidate genes and pathways orchestrating the response to metal stress in Noccaea hyperaccumulators. Our study highlights several species-specific traits linked to the detoxification of metals and metal-induced oxidative stress in hyperaccumulating N. praecox when compared to a closely related model species, N. caerulescens, when grown in the field. Transcriptome analysis revealed distinct differences between the three studied natural Noccaea populations. Notably, we observed several pathways frequently connected to metal stress, i.e., glutathione metabolism, phenylpropanoid biosynthesis, and flavonoid biosynthesis, which were enriched. These differences were observed despite the relative evolutionary closeness of studied species, which emphasizes the importance of further expanding our knowledge on hyperaccumulators if we want to exploit their mechanisms for phytoremediation efforts or food quality improvements.